2019
DOI: 10.12659/msm.914579
|View full text |Cite
|
Sign up to set email alerts
|

miR-30c-5p Reduces Renal Ischemia-Reperfusion Involving Macrophage

Abstract: Background Ischemia-reperfusion (I/R) leads to kidney injury. Renal I/R frequently occurs in kidney transplantations and acute kidney injuries. Recent studies reported that miR-30 stimulated immune responses and reductions in renal I/R related to anti-inflammation. Our study investigated the effects of miR-30c-5p on renal I/R and the relationship among miR-30c-5p, renal I/R, and macrophages. Material/Methods Sprague Dawley rats received intravenous tail injections of mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 35 publications
0
19
0
Order By: Relevance
“…miR-30: As described ahead, miR-30 preserved mitochondrial morphology and inhibited cell apoptosis in I/R-induced AKI rat model [24]. miR-30c has been shown to target Bnip3L and Hspa5, thereby inhibiting cisplatin-induced tubular epithelial cell apoptosis [48]. In addition, He et al reported that miR-30a is associated with the inhibition of UUO-induced renal fibrosis under MSC-EVs treatment [28].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 92%
See 1 more Smart Citation
“…miR-30: As described ahead, miR-30 preserved mitochondrial morphology and inhibited cell apoptosis in I/R-induced AKI rat model [24]. miR-30c has been shown to target Bnip3L and Hspa5, thereby inhibiting cisplatin-induced tubular epithelial cell apoptosis [48]. In addition, He et al reported that miR-30a is associated with the inhibition of UUO-induced renal fibrosis under MSC-EVs treatment [28].…”
Section: Versatile Msc-evs-derived Mirnas Modulate Renal Injury and Hmentioning
confidence: 92%
“…The mechanism regulating cell apoptosis is one of the most important aspects of renal protection. Indeed, the anti-apoptotic pathway has been reported in many studies with MSC-EVs treatment in a variety of rodent renal injury models, including AKI induced by I/R [24,31,33,104,106,[116][117][118]120,124,125], cisplatin [48,119,126], gentamicin [105], and glycerol [17], hypoxia-induced renal injury [60], aldosterone-induced renal injury [52], and UUO-induced CKD model [109]. Recent advances have gradually uncovered the specific miRNAs, their targets and signaling pathways involved in the effect of anti-apoptosis (Table 2), including PTEN, AKT, mTOR, dynamin-related protein 1 (DRP1), Sema3A, and ERK signaling pathway.…”
Section: Renal Protectionmentioning
confidence: 99%
“…Yang et al (2020) showed that the M2 polarization of tumor-associated macrophages could be promoted by long noncoding RNA (lncRNA) RP11-361F15.2 through miR-30c-5p. A miR-30c-5p agomir might contribute to the transformation of M1 macrophages to M2 macrophages, resulting in changes in inflammatory cytokine levels (Zhang et al, 2019). A recent study showed that miR-16-5p mimics significantly decreased the mRNA expression of IL-1β, IL-6, and TNF-α under LPS stimulation conditions, which indicated that miR-16-5p might be a critical factor involved in the antiinflammatory effects (Yamada et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Another study also determined that miR-204 reduce the IL-6R expression to alleviate LPS-induced mesangial cell apoptosis and oxidative stress accumulation in SAKI [ 13 ]. Of interest, miR-30c-5p, which has been proved as an essential mediator of kidney injury, was able to inhibit the expression of tumor necrosis factor-alpha (TNF-α) and multiple inflammatory cytokines in rats [ 14 , 15 ]. Overexpression of miR-30c-5p could also significantly increase human renal tubular epithelial cells (HK-2 cells) apoptosis to inhibit kidney stones formation [ 16 ].…”
Section: Introductionmentioning
confidence: 99%